Psychosocial Interventions in Bipolar Disorder - Yılmaz Gülsüm (International Journal of Psychotherapy Practice and Research, 2025)
Bipolar disorder is a chronic condition marked by episodes of mania and depression, significant functional impairment, and challenges with treatment adherence. Current guidelines highlight the importance of both medication and psychosocial approaches in treatment. This review explores the primary psychosocial interventions for bipolar disorder. Psychoeducation helps recognize early symptoms, improves medication compliance, and prevents relapses. It is simple to implement and cost-effective. Family-Focused Therapy (FFT) enhances family communication, reduces emotional expression, and lowers the frequency of depressive episodes. Interpersonal and Social Rhythm Therapy (IPSRT) supports maintaining social stability by addressing disturbances in biological rhythms. Cognitive Behavioral Therapy (CBT) decreases depressive symptoms and boosts treatment adherence by restructuring automatic thoughts. Additionally, cognitive and functional rehabilitation programs improve attention, memory, and executive functioning. Peer support groups and digital e-health tools, though supportive, have limited evidence of effectiveness. In summary, multicomponent psychosocial interventions serve as a valuable addition to medication, helping to prevent relapses, improve functioning, and enhance quality of life in individuals with bipolar disorder.
Keywords: Bipolar disorder